A Comprehensive Review of the Transformative Impact of Artificial Intelligence on Sustainable Development - Sri Widiastuti; Loso Judijanto; Tanwir Tanwir; Arnes Yuli Vandika; Abdul Muid Fabanyo (Edujavare Publishing, 2022)
This comprehensive review article examines the transformative impact of Artificial Intelligence (AI) on Sustainable Development, covering diverse sectors such as environmental conservation, energy efficiency, healthcare, and socio-economic inclusion. The integration of AI technologies has the potential to revolutionize traditional practices and contribute significantly to achieving sustainable development goals. The primary objective is to comprehensively analyze AI's transformative impact across various domains of sustainable development, highlighting key applications, challenges, and future trends. The research methodology involves a Systematic Literature Review (SLR) approach, encompassing a structured search, selection, and analysis of relevant scholarly articles, reports, and studies on AI and sustainable development. The findings reveal that AI is crucial in environmental monitoring, energy optimization, healthcare innovation, and socio-economic inclusion. However, ethical considerations, data privacy, and regulatory frameworks are essential aspects to address for responsible AI deployment in sustainable development initiatives.